1978
DOI: 10.1107/s0567739478002065
|View full text |Cite
|
Sign up to set email alerts
|

Difference Fourier refinement of metaquohemerythrin

Abstract: A model for metaquohemerythrin from Themiste dyscritum has been refined in the crystallographic sense of the term by difference Fourier methods at 2.8 and 2.5 ,/~ resolution. Fourteen cycles of refinement reduced R from an initial value of 0.385 for the 9461 reflections from I0 to 2.8/k to 0.253 for 16 363 reflections from 10 to 2-5 A resolution. On the basis of peaks in difference maps, 49 water molecules have been added to the model for a total of 3833 atoms in the asymmetric unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Crystallographic studies based on difference Fourier maps of K2HgI4-treated T. dyscritum hemerythrin yield further evidence for mercury-sulfur coordination. Figure 2 contains a stereoview of the difference electron density at 2.8-Á resolution near cysteine-50, superimposed on the protein model refined at 2.5-Á resolution (Stenkamp et al, 1978a). The elongated shape of the difference density indicates that the bound mercurial is Hg-I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallographic studies based on difference Fourier maps of K2HgI4-treated T. dyscritum hemerythrin yield further evidence for mercury-sulfur coordination. Figure 2 contains a stereoview of the difference electron density at 2.8-Á resolution near cysteine-50, superimposed on the protein model refined at 2.5-Á resolution (Stenkamp et al, 1978a). The elongated shape of the difference density indicates that the bound mercurial is Hg-I.…”
Section: Resultsmentioning
confidence: 99%
“…Difference electron density maps were calculated using X-ray diffraction data from isomorphous crystals of metaquohemerythrin and K2HgI4-treated metaquohemerythrin from T. dyscritum. The metaquohemerythrin data were those used in the refinement of the protein model at 2.5-Á resolution (Stenkamp et al, 1978a). The data for K2HgI4-treated hemerythrin (Stenkamp et al, 1976) were reprocessed to include the 2 dependence of the radiation decay and yielded 10526 reflections with I > 2 ( ) out to 2.8-Á resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycylglycine monohydrochloride monohydrate (Parthasarathy, 1969) L-alanylalanine monohydrochloride (Tokuma et al, 1969), L-O-serine phosphate , DL-0-serine phosphate monohydrate , La-ydiaminobutyric acid monohydrochloride (Naganathan 8~ Venkatesan, 1971), L-alanylglycine lithium bromide dihydrate (Declercq et ul., 1971), potassium L-tyrosineOsulfate dihydrate (Fries & Sundaralingam,197 l), glycyl-L-alanyl monohydrochloride (Naganathan & Venkatesan, 1972), di-L-leucine monohydrochloride (Golie & Hamilton, 1972), glycylglycine phosphate monohydrate (Freeman et ul., (1972), N-acetyl-L-phenylalanyl-L-tyrosine (Stenkamp & Jensen, 1973), glycylglycine nitrate , penicillamine monohydrochloride monohydrate (Rao e l al., 1973), Lcysteine (Kerr & Ashmore, 1973), 3-hydroxyphenylalanine (Byrkjedal et ul., 1974), ~-3,4dihydroxyphenylalanine monohydrochloride (Mostad & RQmming, 1974), glycyl-L-tyrosine dihydrate and N-acetyl-L-tyrosine methylamide (Cotrait & Bideau, 1974), diglycine sulfate monohydrate (Cano & Martinez-Camera, 1974), ammonium glycinium sulfate (Vilminot et al, 1974), N-acetyl-L-tryptophan methyl ester (Cotrait & Barrans, 1974), DL-alanyl-DL-methionine (Stenkamp & Jensen, 1974), glycyltleucine (Pattabhi etul.. 1974), 3 3'4hiodialanine dihydrochloride (Rosenfield & Parthasarathy, 1974), glycyl-DL-threonine monohydrate (Swaminathan, 1979, Lmethionyl-methionine (Stenkamp & Jensen, 1975, DLallothreonine hydrobromide, (Swaminathan & Srinivasan, 1979, glycine nitrate (Narayanan & Venkataraman, 1975), benzoyl-DL-leucylglycine ethyl ester (Timmins, 1975), 3,3,3',3'-tetramethyl-Dcystine dihydrochloride monohydrate (Vijayalakshmi & Srinivasan, 1975u), L-alanylalanylalanine monohydrate (Fawcett e l ul., 1979, DLtryptophan ethyl ester hydrochloride (Vijayalakshmi & Srinivasan, 1975b), D-auo-isoleucine monohydrochloride monohydrate (Varughese & Srinivasan, 1976), allo4-hydroxy-~-proline dihydrate (Shamala et ul., 1976), cyclo(-Lprolyl-D-phe...…”
Section: Other Amino Acids and Peptidesmentioning
confidence: 99%
“…search of the Cambridge Structural Database (CSD, version 5.45, Update 1, March 2024;Groom et al, 2016) revealed that no crystal structures were reported for either Gly-Met or Met-Gly. Other dipeptides containing methionine have been reported, including l-Ala-l-Met hemihydrate(Gorbitz, 2003), dl-Ala-ld-Met(Jha et al, 2020), l-Pro-l-Met monohydrate(Padmanabhan & Yadava, 1983), l-Met-l-Met(Stenkamp & Jensen, 1975), l-Met-l-Ala (Gorbitz, 2000), and l-Met-l-Ser(Gorbitz et al, 2006).…”
mentioning
confidence: 99%